Pengaruh Disiplin Kerja dan Pelatihan Kerja terhadap Kinerja Karyawan Satpam PTPN 1 Pulau Tiga - Anna Sovia; Dias Setia Ningsih; Dhian Rosalina (Akuntansi, 2024)
To determine the influence of, work discipline and job training on the performance of security personnel at PTPN 1 Pulau Tiga. The method used in this research is a quantitative method. The population in this study consists of all security personnel at PTPN 1 Pulau Tiga, totaling 35 individuals. The sampling technique used in this research is saturated sampling, meaning that all security personnel at PTPN 1 Pulau Tiga are included as the sample. The data analysis methods used are multiple linear regression analysis, t-test, F-test, and coefficient of determination test. (Adjusted R2).